1983
DOI: 10.1139/v83-413
|View full text |Cite
|
Sign up to set email alerts
|

Ozonolysis of vinyl chloride in methanol: a convenient entry to methoxymethylhydroperoxide and its chemistry

Abstract: Ozonolysis of vinyl chloride (7) in methanol at −78 °C afforded methoxymethylhydroperoxide (10) in high yield along with only trace amounts of methyl formate (14). The former (10) was converted into a mixture of methyl formate (14) as the major and dimethylformal (18) as the minor product by HCl-catalysis in methanol. Reduction of 10 with dimethylsulfide and subsequent treatment with HCl–methanol gave dimethylformal (18). Partial reduction of 10 with a deficient amount of triphenylphosphine gave formaldehyde h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The above observations [22,24] suggest that CH,-0-CHO observed in this study is due to a heterogeneous reaction. Through the course of this study, it was observed that HCOOH, either formed as a product or added as a reactant, tended to adhere to the reactor wall.…”
Section: Formation Of Compound Z a N D Formic Acetic Anhydride With Tsupporting
confidence: 61%
See 2 more Smart Citations
“…The above observations [22,24] suggest that CH,-0-CHO observed in this study is due to a heterogeneous reaction. Through the course of this study, it was observed that HCOOH, either formed as a product or added as a reactant, tended to adhere to the reactor wall.…”
Section: Formation Of Compound Z a N D Formic Acetic Anhydride With Tsupporting
confidence: 61%
“…Through the course of this study, it was observed that HCOOH, either formed as a product or added as a reactant, tended to adhere to the reactor wall. It is possible, therefore, that the adsorbed HCOOH acted as a proton donor in the CH, -0-CH,OOH conversion mechanism, as described by Meister et al [24].…”
Section: Formation Of Compound Z a N D Formic Acetic Anhydride With Tmentioning
confidence: 95%
See 1 more Smart Citation
“…For accurate spectral measurements to be made, experiments must be performed under conditions where F atoms are converted stoichiometrically into CH30CH202 radicals by the reaction sequence (10) followed by (2): F + CH3OCH3 -CH3OCH2 + HF (10) CH3OCH2 + 02 (+M) -CH30CH202 (+M) (2) Several potentially interfering reactions may be identified, and their possible effect must be considered; F + Oz (+M) -F02 (+M) (14) F + CH3OCH2products (15)…”
Section: Self Reaction Kinetics and Uv Absorptionmentioning
confidence: 99%
“…The salts were filtered off and the filtrate was concentrated at room temperature and 12 Tom; 'H nmr analysis (CDC13, TMS) of the liquid residue (2 mL) showed the presence of 21 and 22 (6 4.98, s, CHI) (14) in a ratio of 1:0.9. By flash chromatography (column 2 X 30 cm, 50 g silica gel, dichloromethane), 60 mg (31%) of 21 was isolated.…”
Section: Ozonolysis Of Z2b In Ch30dmentioning
confidence: 99%